A Theoretical Study on the Medicinal Properties and Eletronic Structures of Platinum(IV) Anticancer Agents With Cl Substituents - Yan, Xiaoyang; Gao, Hongwei (Frontiers in Oncology, 2022)
In this paper, we selected Pt(en)Cl4, Pt(dach)Cl4, and Pt(bipy)Cl4 with gradually increasing ligands to explore the ligand effect on the properties of platinum(IV) anticancer drugs. The electronic structures and multiple drug properties of these three complexes were studied at the LSDA/SDD level using the density functional theory (DFT) method. By comparing the gap between the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO), electron affinity, atomic charge population, and natural bond orbital (NBO), we found that the order of reducibility is Pt(bipy)Cl4 > Pt(en)Cl4 > Pt(dach)Cl4. Our research can provide the theoretical basis for the development of anticancer drugs.